Charge transfer complexes as colour changing and disappearing–reappearing colour materials. (7th May 2019) - Sharada, Durgam; Saha, Arijit; Saha, Binoy K.
Abstract : Charge transfer complexes, made of suitably chosen electron-rich and electron-deficient components, can perform as vanishing colour, disappearing–reappearing colour and colour changing materials. Abstract : Here it has been demonstrated that simple charge transfer complexes, which are produced through a proper selection of the individual components, can be used as vanishing colour, disappearing–reappearing colour and colour changing materials under ambient conditions.